Analisis Pemahaman Konsep Kimia Materi Larutan Penyangga pada Siswa Kelas XI Kelompok A SMAN 7 Mataram - Irma Fitri Cahyati; I Nyoman Loka; Mukhtar Haris (FKIP University of Mataram, 2026)
This study aims to determine the level of conceptual understanding and analyze the difficulties faced by class XI Group A students of SMAN 7 Mataram in understanding the concept of buffer solutions. The type of research used is descriptive quantitative. The study was conducted in class XI A3 and XI A4 with a total of 65 students. Data were collected using a Two Tier Multiple Choice (TTMC) test instrument with 17 valid questions. The results of this study are the level of understanding of the chemical concept of buffer solutions of class XI students of SMAN 7 Mataram is 61.1% which is classified as moderate, with the distribution of conceptual understanding being quite a lot of students who understand the concept (43.6%), a few students who have misconceptions (35.0%) and do not understand the concept (21.4%). The conceptual understanding of class XI A3 students in each sub-material of buffer solutions with the highest category being quite a lot of students who understand the concept (58.1%) in the material of the definition of buffer solutions, quite a lot of students who have misconceptions (52.4%) in the material of types and components of buffer solutions, and quite a lot of students who do not understand the concept (45.7%) in the material of differences in buffer solutions. The conceptual understanding of class XI A4 students in each sub-material of buffer solutions with the highest category is quite a lot of students who understand the concept (51.1%) in the material on the definition of buffer solutions, quite a lot of students have misconceptions (43.4%) in the material on the working principles of buffer solutions, and a few students who do not understand the concept (23.5%) in the material on the role of buffer solutions in the human body.